Readability Laporan Tahunan Dan Audit Delay - Shyntia Alvenia; Annisaa Rahman (InFestasi, 2022)
The purpose of this study is to examine the effect of readability of annual reports on audit delays. The research period is 2018-2019, with a sample of 1143 companies listed on the Indonesia Stock Exchange. The readability of the annual report is measured by the size of the report file, where the larger the file size of the annual report, the lower the readability of the annual report. Audit delay is measured by the number of days of issuance of the audit report calculated from the end of the fiscal year. The results of this study indicate that readability of annual report has a negative effect on audit delays. This means that the low readability of the annual report affects audit delays. The results of this study support agency theory. There are indications of management's motivation in manipulating the annual report by reducing the readability of the report, making the auditors have to be careful in conducting audits so that they seem to experience delays in issuing audit reports.Penelitian ini bertujuan untuk menguji pengaruh keterbacaan laporan tahunan terhadap audit delay. Periode penelitian 2018-2019, dengan sampel sebanyak 1143 perusahaan yang terdaftar di Bursa Efek Indonesia. Keterbacaan laporan tahunan diukur dari ukuran file laporan, semakin besar ukuran file laporan tahunan maka semakin rendah tingkat keterbacaan laporan tahunan. Audit delay diukur dengan jumlah hari penerbitan laporan audit yang dihitung sejak akhir tahun anggaran. Hasil penelitian ini menunjukkan bahwa keterbacaan laporan tahunan berpengaruh negatif terhadap audit delay. Rendahnya keterbacaan laporan tahunan mempengaruhi audit delay. Hasil penelitian ini mendukung teori keagenan. Adanya indikasi motivasi manajemen dalam memanipulasi laporan tahunan dengan mengurangi keterbacaan laporan, membuat auditor harus berhati-hati dalam melakukan audit sehingga terkesan mengalami keterlambatan dalam mengeluarkan laporan audit.